Investigation into the characteristics of multiphase transient combustion and flow within a two-stage propulsion framework - Guo, Junting; Yu, Yonggang; Zhang, Xinwei (Physics of fluids (1994), 2025)
The intricate propulsion structure of cased telescoped ammunition (CTA) gives rise to intense spatiotemporal pulsations in the release of propellant combustion energy, thereby exerting a substantial influence on the dynamic stability of launching process. For the purpose of thoroughly exploring the gas–solid mixing and unsteady combustion processes within the irregular space, an advanced two-dimensional axisymmetric gas–solid reactive flow model of CTA is developed. The k-ε turbulence model is utilized for depicting the two-phase turbulent mixing characteristics, and the nonlinear coupling of the internal flow field combustion and the dynamic impact extrusion calculation is achieved through the dynamic mesh theory and User Defined Function. A numerical simulation is conducted regarding the propulsion process of 105 mm CTA. The time span commencing from the ignition of propellants and concluding when the projectile leaves the muzzle totals 6.8 ms, with the dynamic impact extrusion process persisting for 1.38 ms. The intense combustion of main-charge propellants causes the chamber pressure to increase, with the pressure peak reaching 508 MPa. The high-pressure combustion gas forms annular vortices during its convergence toward the initial gas region, further enhancing the gas–solid mixing and propellant combustion. Subject to the influence of interphase drag force, the main-charge propellant bed undergoes a violent collapse along the axial and radial directions.